Skills development for sustainable career planning in Bangladesh: the case of gender equality in education - Md Jahangir Alam; Md Abul Hafaz; Firuz Humayra Methe (Quality Education for All)
Purpose – This study aims to investigate the importance of lifelong learning in cultivating competent human capital, fostering long-term career sustainability and promoting gender equality in Bangladesh. Design/methodology/approach – This study has used a qualitative research methodology with inductive reasoning. The researchers used purposive sampling to conduct semi-structured interviews with 34 male and female students at the graduate and undergraduate levels, in addition to six stakeholders. This research is grounded in the theoretical frameworks of human capital development theory and gender and development theory. Findings – The results suggest that there exists a positive correlation between lifelong learning, sustainable career development and gender equality in the context of Bangladesh. Successfully executing strategies might also play a significant role in attaining Bangladesh’s sustainable development goals (SDGs). Practical implications – Educational curriculum reform within institutions is urgently needed, necessitating the active involvement and influential contributions of actors and stakeholders. Implementing lifelong learning must also align with gender equality and SDGs. Originality/value – This study addresses a significant gap in the existing literature by offering insights into the relationship between lifelong learning, career sustainability and gender equality within the specific context of Bangladesh. This study provides valuable contributions to scholars, stakeholders and policymakers while establishing a foundation for future research endeavors.